The Effect of Combined Slow Deep Breathing and Zikr on Family Anxiety in the ICCU of Dr. Soehadi Prijonegoro Regional Hospital, Sragen - Animah, Fitri Rat; indriyati; Putra, Fajar Alam (Bantayang Omni Cendekia, 2025)
Background: Based on data from the Medical Records of patients in the ICCU (Intensive Cardiology Care Unit) of dr. Soehadi Prijonegoro Hospital, Sragen, the number of new patients increased from 388 in 2023 to 537 in 2024 (38.4%). The death rate in the ICCU Room from January to December 2024 was 102 people (18.9%). A preliminary survey showed that 7 out of 10 patient families (70%) experienced anxiety symptoms. To date, slow deep breathing and dhikr have not been applied by patient families to reduce anxiety. The combination of dhikr and slow deep breathing is a therapy that can relieve anxiety. Objective: This study aimed to determine the effect of the combination of slow deep breathing and dhikr on anxiety levels in families of patients in the ICCU Room of dr. Soehadi Prijonegoro Hospital, Sragen. Methods: This study used a quantitative approach with a pre-experimental design (one-group pretest–posttest). The sample consisted of 41 families of ICCU patients, selected using a purposive sampling technique. The instrument used was the HARS (Hamilton Anxiety Rating Scale) questionnaire. Data were analyzed using the Wilcoxon test. Results: The statistical test results showed a significant effect of the combination of slow deep breathing and dhikr on family anxiety levels in the ICCU Room of dr. Soehadi Prijonegoro The combination of slow deep breathing and dhikr effectively reduced anxiety among patient families in the ICCU Room of dr. Soehadi Prijonegoro Hospital, Sragen, and may be considered as a complementary approach in anxiety management.